Emotion Processing for Arousal and Neutral Content in Alzheimer's Disease. (10th December 2009) - Satler, Corina; Uribe, Carlos; Conde, Carlos; Da-Silva, Sergio Leme; Tomaz, Carlos
Abstract : Objective . To assess the ability of Alzheimer's disease (AD) patients to perceive emotional information and to assign subjective emotional rating scores to audiovisual presentations. Materials and Methods . 24 subjects (14 with AD, matched to controls for age and educational levels) were studied. After neuropsychological assessment, they watched a Neutral story and then a story with Emotional content. Results . Recall scores for both stories were significantly lower in AD (Neutral and Emotional:P = .001 ). CG assigned different emotional scores for each version of the test, P = .001, while ratings of AD did not differ, P = .32 . Linear regression analyses determined the best predictors of emotional rating and recognition memory for each group among neuropsychological tests battery. Conclusions . AD patients show changes in emotional processing on declarative memory and a preserved ability to express emotions in face of arousal content. The present findings suggest that these impairments are due to general cognitive decline.